A Case Series of Psychological Stress Evaluation as a Risk Factor for Oral Lichen Planus. (6th October 2022) - Sufiawati, Irna; Megawati, Ani; Al Farisyi, Muhammad; Putra, I. Nyoman Gede Juwita
Abstract : Introduction . Oral lichen planus (OLP) is a chronic inflammatory disease of the oral mucosa with unknown etiology. Suggested predisposing factors for the development of OLP include genetic factors, viral infections, psychological stress, trauma, drug intake, and some systemic diseases. This serial case aimed to evaluate the psychological stress in triggering various types of OLP and its management. Case Report . Six patients, four females and two males with an age range from 23 to 57 years, came to an oral medicine clinic with chief complaints of chronic pain and burning sensations in the oral cavity. All cases showed typical clinical features of OLP on the oral mucosa, including reticular, plaque-like, erosive, and ulcerative lesions. An incisional biopsy was performed in some cases and the histopathology features confirmed the diagnosis of OLP with no signs of dysplasia/malignancy. According to the Depression, Anxiety, Stress Scale (DASS)-21, the patients had different levels of depression ranging from mild to severe; 3 patients were considered to have moderate anxiety and others had severe anxiety; and 5 patients experienced mild stress and 1 patient had moderate stress. The patients were given corticosteroids, supportive therapy, and psychological counseling. All patients experienced significant improvement of the lesions after treatment. Conclusion . Psychological stressors play an essential role as a risk factor in the development of OLP. Therefore, management of OLP encompasses not only an appropriate treatment of the lesions but also psychological intervention.